Ethnobotany of medicinal plants and traditional rituals community of Sembalun Village, East Lombok - Hidayani Hidayani; Gito Hadiprayitno; Kusmiyati Kusmiyati; Jono Irawan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
The used of plant species by the community is an inseparable unit in everyday life. The plants used by the community in Sembalun Village for medicines and traditional rituals has been attached and is a hereditary tradition. Community knowledge about the use of plants for medicines and traditional rituals has not been well documented. The purpose of this study was to determine the species of medicinal plants and traditional rituals, as well as to find out the parts of plants used by the community in Sembalun Village. This type of research is descriptive qualitative through direct observation and interviews were conducted on 33 respondents using descriptive methods and purposive sampling observation techniques. The results showed that 58 species of medicinal plants from 30 families and 5 species of plants for traditional rituals from 5 families were used by the people of Sembalun Village. These medicinal plant species are believed to cure 28 types of diseases and are used in the traditional rituals of Sembe, Ngeayu-ayu, Bebije Tawar, and the use of Soyot (Sapindus rarak) in washing traditional Bale Lokak clothes. The most widely used plant parts were leaves as many as 21 species and the least used were seeds and flowers as many as 1 plant species.